Remotely Monitored Home-Based Neuromodulation With Transcranial Alternating Current Stimulation (tACS) for Mal de Débarquement Syndrome - Cha, Yoon-Hee; Riley, Jeff; Gleghorn, Diamond; Doudican, Benjamin (Frontiers in Neurology, 2021)
Objective: To determine whether remotely-monitored transcranial alternative current stimulation (tACS) may be a viable and safe treatment option for Mal de Débarquement Syndrome (MdDS). Background: Mal de Débarquement Syndrome is a neurotological disorder characterized by persistent oscillating vertigo that is triggered by entrainment to passive oscillatory motion such as occurs during water-based travel. Treatment options for MdDS are limited, variably effective, and can be undone by further travel. Deisgn/Methods: This was a remotely-monitored open-label optional extension phase of a double-blind randomized onsite study of tACS for medically refractory MdDS. The primary goal was to determine safety, feasibility, and blinded participant feedback. The secondary goal was to determine efficacy. Thirteen participants (all women), aged 22-67 years experiencing a duration of illness of 11-72 months, were a subset of 24 individuals who participated in an on-site study of tACS. They had either not responded to the on-site protocol or relapsed after travel home. Treatment accessories and a tablet controlled tACS stimulator (Pulvinar-XCSITE-100) were mailed to participants. Three teaching sessions were performed via webcam followed by on-going remote monitoring of treatment logs and participants’ reports through a daily on-line diary and weekly questionnaires. Treatment continued until an effective protocol was administered for 4 weeks and then tapered over 4 weeks. Participants completed a blinded feedback survey and a debriefing interview at the completion of the entire study. Results: Treatment duration ranged from 4-31 weeks followed by a four-week taper accounting for 578 verified sessions. Of the 13 total participants, seven agreed or agreed strongly in the blinded survey that tACS treatment was beneficial; 2) Twelve were comfortable utilizing tACS on their own; 3) Eleven preferred stimulation above their individual alpha frequency; 4) Side effects were generally mild and typical of tACS. In the debriefing interview completed 2-9 months after the last stimulation, five participants reported doing “great,” with no to minimal symptoms, four reported doing “good,” with moderate symptoms, and four reported no change compared to pre-study baseline. Conclusion: Remotely-monitored tACS may be a safe treatment option for MdDS with the potential for lasting outcomes, increased accessibility, and reduction in travel-related treatment reversal.